Psychosocial stressors and cardiovascular disease risk among community health workers in Fika, Yobe State, Nigeria - Jacob, Akinniyi Rotimi (Tanjong Malim, 2024)
Psychosocial stressors and cardiovascular disease risk among community health workers in Fika, Yobe State, Nigeria by Jacob, Akinniyi Rotimi